MODIS Learning Media: An Effort to Enhance Students’ Self-Regulated Learning and Critical Thinking - Mei Anggun Devina; Madziatul Churiyah; Ardian Novianti (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2026)
The role of learning media in the world of education has an important role in improving students’ self-regulated learning and critical thinking skills. This research and development aim to create a MODIS learning media through validation by media experts and material experts to improve self-regulated learning and critical thinking on the elements of Basic Job Skills, K3, and Work Culture, Data and Information material topics, class X MPLB. This research and development use the ADDIE model, namely analyze, design, development, implementation, and evaluation. This research and development collected quantitative and qualitative data, the subjects of the trial included 35 students of class X MPLB at SMK Negeri 1 Malang. The data analysis technique of self-regulated learning and critical thinking uses the average value of the percentage. This research and development produce MODIS learning media assisted by google sites with various features that are integrated with materials and assignments that will provide a more varied learning experience. Research and development show that the validation results of material experts and media experts are very feasible to use so that they can significantly increase students’ self-regulated learning and critical thinking in learning.